Combined treatment of umbilical cord Wharton’s jelly-derived mesenchymal stem cells and platelet-rich plasma for a surgical patient with hospital-acquired pressure ulcer: a case report and literature review - Zhou, Changhui; Jiao, Linlin; Qiao, Xiaoping; Zhang, Weiwei; Chen, Shuangfeng; Yang, Chunling; Meng, Min (Frontiers in Bioengineering and Biotechnology, 2024)
Hospital-acquired pressure ulcers (HAPUs) are still an important worldwide issue related to safety and quality of patient care, which are among the top five adverse events reported. Patients who develop HAPUs have longer stays in the hospital than necessary, and they are at greater risk of infections and are more likely to die. Surgical patients are prone to developing PUs because they often remain immobile for extended periods of time and their surgical procedures may limit the flow of blood oxygen and nutrition, and lead to a decrease in muscle tone. Mesenchymal stem cells (MSCs) represent an attractive stem cell source for tissue regenerative in clinical applications, which have been demonstrated to improve wound healing through reepithelialization, increased angiogenesis, and granulation tissue formation. Here, we present a case of an emergency surgical patient who developed a ulcer on the right heel during hospitalization. The human umbilical cord Wharton's jelly-derived MSCs (WJ-MSCs) resuspended in platelet-rich plasma (PRP) were injected into ulcer margins. Four days after WJ-MSCs application the patient showed a progressive healing of PU. On the 4th to 33th day, granulation tissue formation and reepithelialization were clearly visualized. The ulcer was were almost healed completely on the day 47, and the pain in the patient's wound area has also decreased. Thus, intradermal transplantation of WJ-MSCs and PRP was safe and effective for treatment in patient with pressure ulcer. WJ-MSCs together with PRP may offer a promising treatment option for wound healing.